Alexithymia as a mediator between adverse childhood events and the development of psychopathology: a meta-analysis - Kick, Lorenz; Schleicher, Daniel; Ecker, Angelika; Kandsperger, Stephanie; Brunner, Romuald; Jarvers, Irina (Frontiers in Psychiatry, 2024)
Introduction Victims of child abuse have an elevated risk of developing mental health issues later in life. Several variables have been suggested as mediators of this correlation, but little is known about the possible influence of alexithymia. Alexithymia is a sub-clinical personality trait that manifests as difficulties recognizing and verbalizing emotions. Methods In this study, two separate meta-analyses were conducted using questionnaire data, and Pearson correlations for overall effects were estimated. Results The correlation between child abuse and alexithymia showed to be significant (r = .26), as did the correlation between alexithymia and general psychopathology (r = .44). Further analyses revealed no indication for possible publication bias. When investigating differences between various subtypes of child maltreatment, each subtype significantly correlated with alexithymia. Emotional abuse, emotional neglect, and physical neglect had stronger correlations than physical and sexual abuse. Discussion These results suggest that alexithymia plays a mediating role, at least in part, in the relationship between experiences of child abuse and general psychopathology in adulthood. Therefore, alexithymia may be relevant to further research and deserves attention in the prevention of and therapy for mental health issues in victims of child abuse.